Analysis of Road User Satisfaction Passing Through The West Boulevard Highway and The Kelapa Gading - Pulo Gebang Toll Road - Andhika Putri, Lisa; Pontan, Darmawan; Moengin, Parwadi; Inavonna, Inavonna (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the satisfaction level of road users on Jalan Boulevard Barat Raya and the Kelapa Gading - Pulo Gebang Toll Road. Evaluating user satisfaction is crucial for assessing transportation infrastructure performance and prioritizing road maintenance and development. Using a quantitative approach, data was collected through questionnaires distributed to drivers and passengers of private and online four-wheeled vehicles. The research applied the Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methods, focusing on nine indicators from the Indonesian Ministerial Regulation No. 14 of 2017, including requirements, procedures, completion time, costs, service specifications, implementer competence, behavior, complaint handling, and facilities. The CSI results revealed that road users are "Very Satisfied" with both roads, with Jalan Boulevard Barat Raya scoring 90.7% and the Kelapa Gading - Pulo Gebang Toll Road scoring 90.85%. However, IPA analysis identified several variables in quadrant 1, indicating high importance but low performance. These variables include: (B1) reasonable tariffs without additional costs, (PP1) friendly and polite officers handling complaints, (SM1) availability of complaint forums, and (SP1) adequate supporting facilities. These findings highlight areas needing improvement to enhance user satisfaction further. Overall, the study underscores the importance of addressing specific service gaps to maintain high satisfaction levels among road users.